DETERMINING TRAVEL DELAY OF VEHICLES QUEUE AT A TRAFFIC SIGNAL - Cahyono, Setiyo Daru; Tristono, Tomi; Aji, Seno; Utomo, Pradityo (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Mathematical modelling assumes that the vehicle’s volume has a uniform pattern. Due to traffic lights settings, the number of vehicles queue grows linearly. The reality, the stochastic arrivals of the vehicles could be (1) in the randomized arrivals, (2) in the form of groups/ platoon, or (3) in the mixed arrivals. It is observed that the arrival of the vehicles in the queue tends to have a normal pattern. The objective of this research is to study the implications of the arrival categories to the travel delay. For simulation, it uses the numerical method referring to the real state. The result indicates, determining travel delay become precise for all vehicles. It is due to the travel delay formula is represented as a discrete function. The arrival time, departure time, and stop time for each vehicle at the signalized intersection are recorded in the device